An improved lower bound and approximation algorithm for binary constrained quadratic programming problem - Lu, Cheng; Wang, Zhenbo; Xing, Wenxun (Journal of global optimization, 2010)
This paper presents an improved lower bound and an approximation algorithm based on spectral decomposition for the binary constrained quadratic programming problem. To decompose spectrally the quadratic matrix in the objective function, we construct a low rank problem that provides a lower bound. Then an approximation algorithm for the binary quadratic programming problem together with a worst case performance analysis for the algorithm is provided.